2013
DOI: 10.1262/jrd.2012-157
|View full text |Cite
|
Sign up to set email alerts
|

Vitreous Cryopreservation of Human Preantral Follicles Encapsulated in Alginate Beads with Mini Mesh Cups

Abstract: To completely avoid ice crystal formation and thus get a higher survival rate, vitrification methods have been commonly used for cryopreservation of oocytes and embryos. However, currently used vitrification methods for oocytes and embryos are not suitable for the cryopreservation of preantral follicles (PFs). In the present study, stainless steel mesh was fabricated into mini mesh cups to vitrify isolated PFs. Moreover, isolated follicles were encapsulated and then subjected to vitreous cryopreservation to fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 45 publications
3
12
0
Order By: Relevance
“…In mice, isolated preantral follicles vitrified and treated with propidium iodide (PI) showed a decrease of 11 % in their viability (Trapphoff et al 2010). The viability of isolated follicles vitrified and in vitro-cultured found in our study was similar to that reported for human follicles (Bian et al 2013). In Follicle-Vit, the proportion of viable follicles decreased with time in culture compared to fresh follicles.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In mice, isolated preantral follicles vitrified and treated with propidium iodide (PI) showed a decrease of 11 % in their viability (Trapphoff et al 2010). The viability of isolated follicles vitrified and in vitro-cultured found in our study was similar to that reported for human follicles (Bian et al 2013). In Follicle-Vit, the proportion of viable follicles decreased with time in culture compared to fresh follicles.…”
Section: Discussionsupporting
confidence: 89%
“…Our data show that secondary follicles from Follicle-Vit had diameter and daily growth rate in vitro similar to those seen in non-vitrified, cultured follicles, similar to the results reported for human follicles (Bian et al 2013). On the other hand, follicles from Tissue-Vit had slower growth compared to cultured follicles not subjected to prior vitrification.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Vitrification is a relatively inexpensive procedure and does not require any special instrument [10]. Ovarian tissue vitrification has been performed in mice [11][12][13], domestic animals [14][15][16][17], nonhuman primates [18][19][20], and in humans [21][22][23][24]. To date, no pregnancy has been reported in humans after transplantation of vitrified tissue [3].…”
Section: Introductionmentioning
confidence: 99%
“…At present, cell microencapsulation technology is considered to be a viable therapy. Microencapsulated somatic cells can be used to treat neurological and endocrine diseases, such as diabetes, syndromes after the removal of ovaries, and Parkinson's disease . Microencapsulated stem cells can aid bone regeneration and growth plate injury, repair the myocardium and improve angiogenesis .…”
Section: Introductionmentioning
confidence: 99%